2000
DOI: 10.1023/a:1008348010437
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal vincristine in relapsed non-Hodgkin's lymphomas: Early results of an ongoing phase II trial

Abstract: Liposomal vincristine is active and well tolerated in this heavily pretreated population with relapsed NHL, but can be neurotoxic in a fraction of patients heavily exposed to prior neurotoxic agents. These data, if confirmed, would suggest a potential role for liposomal vincristine in the combination therapy of previously untreated patients with NHL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(48 citation statements)
references
References 12 publications
1
45
0
Order By: Relevance
“…29 ± 31 These findings were subsequently extended and confirmed in Phase I/II clinical trials, which have demonstrated the beneficial effects of liposome encapsulation in regard to improved pharmacokinetics and antitumor activity of liposomal vincristine in humans. 32,33 The improved antitumor efficacy of SALP over free [ S] ODNs is consistent with the increased tumor accumulation and homogeneous distribution of [ S] ODNs within the NG tumors. The broad distribution of SALP/ FITC ± [ S] ODNs within the NG tumor mass was confirmed using LSCM analysis.…”
Section: Discussionmentioning
confidence: 57%
“…29 ± 31 These findings were subsequently extended and confirmed in Phase I/II clinical trials, which have demonstrated the beneficial effects of liposome encapsulation in regard to improved pharmacokinetics and antitumor activity of liposomal vincristine in humans. 32,33 The improved antitumor efficacy of SALP over free [ S] ODNs is consistent with the increased tumor accumulation and homogeneous distribution of [ S] ODNs within the NG tumors. The broad distribution of SALP/ FITC ± [ S] ODNs within the NG tumor mass was confirmed using LSCM analysis.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to the licensed anthracyclines, other liposome-encapsulated cytotoxic agents are undergoing clinical assessment. Examples include various liposomal camptothecins in early-stage clinical trials (16,17) and liposomal vincristine, demonstrating positive results in refractory patient populations (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…15 Clinical studies using VCR encapsulated in distearoylphospatidylcholine/cholesterol (DSPC/Chol) demonstrated that liposomal VCR can be administered at higher doses than free drug and it is effective in relapsed non-Hodgkin's lymphomas (NHL). 16,17 A modification of DSPC/Chol liposomes has been introduced generating the sphingomyelin/cholesterol (SM/Chol) liposomes. The SM/Chol liposomal formulation further improves the pharmacokinetic parameters of VCR, producing an increased VCR accumulation in peritoneal ascitic murine P388 tumors and in solid tumors compared to DSPC/Chol liposome VCR.…”
mentioning
confidence: 99%